Evaluation of Transparency to Improve Good Governance in Pharmaceutical Regulatory Sector of Iran - Yasaman Herandi; Shekoufeh Nikfar; Hossein Bouzarjomehri; Akbar Abdollahiasl (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Improving good governance in the pharmaceutical sector is a valuable priority for improving access to essential medicines. Transparency as a means for good governance was the focus of this study. The objective was to evaluate different sectors of the pharmaceutical regulatory sector of Iran from the aspect of transparency. Awareness of the current situation may assist policymakers in making the right decisions. Methods: The aim of this methodology was to present only quantitative measurement but to gather qualitative information as well. The study was carried from November 2016 to July 2017. The questionnaires of the assessment instrument, which the World Health Organization (WHO) produced for measuring transparency in the public pharmaceutical sector, was used. The interviewees were among managers and staff at different levels of the Food and Drug Administration (IFDA) of Iran and its clients. Results: Medicines registration and distribution of medicines' scores in the 10-point rating system means that they are minimally vulnerable to corruption. Besides, medicine promotion control and procurement of medical products got an acceptable score, which means that they are marginally vulnerable to corruption. On the other hand, qualitative findings and observation of the evidence presented by key informants proved the sufficient legal capacity for transparency in almost all sections. The controversial issue was the 'conflict of interests,' which was not anticipated in some cases. Conclusion: It is valuable to know if Iran's medicine regulatory sector is transparent In order to improve good governance, transparency should be maximized in all sectors, and this is possible by implementing mechanized actions and online tools.